Charting the Road to Competence: Developmental Milestones for Internal Medicine Residency Training - Green, Michael L. (The Accreditation Council for Graduate Medical Education, 2009)
BACKGROUND: The Accreditation Council for Graduate Medical Education (ACGME) Outcome Project requires that residency program directors objectively document that their residents achieve competence in 6 general dimensions of practice. INTERVENTION: In November 2007, the American Board of Internal Medicine (ABIM) and the ACGME initiated the development of milestones for internal medicine residency training. ABIM and ACGME convened a 33-member milestones task force made up of program directors, experts in evaluation and quality, and representatives of internal medicine stakeholder organizations. This article reports on the development process and the resulting list of proposed milestones for each ACGME competency. OUTCOMES: The task force adopted the Dreyfus model of skill acquisition as a framework the internal medicine milestones, and calibrated the milestones with the expectation that residents achieve, at a minimum, the “competency” level in the 5-step progression by the completion of residency. The task force also developed general recommendations for strategies to evaluate the milestones. DISCUSSION: The milestones resulting from this effort will promote competency-based resident education in internal medicine, and will allow program directors to track the progress of residents and inform decisions regarding promotion and readiness for independent practice. In addition, the milestones may guide curriculum development, suggest specific assessment strategies, provide benchmarks for resident self-directed assessment-seeking, and assist remediation by facilitating identification of specific deficits. Finally, by making explicit the profession's expectations for graduates and providing a degree of national standardization in evaluation, the milestones may improve public accountability for residency training.